Religion in Family Firms: A Socioemotional Wealth Perspective on Top-Level Executives with Perceived Religiosity - Fabian Ernst; David Bendig; Lea Puechel (Journal of Business Ethics, 2024)
The extent and mechanisms through which religion intertwines with decision-making processes in family firms remain inadequately understood. Family firm owners, driven by their commitment to ethical business practices and the safeguarding of their socioemotional wealth, actively seek cues to inform their decision-making processes. This research demonstrates that, among these guiding cues, top-level executives' perceived religiosity emerges as a relevant factor. Building upon the socioemotional wealth perspective and conducting a longitudinal analysis based on listed family firms between 2009 and 2018, our findings reveal a positive association between family voting rights and the presence of board members perceived to be religious. Furthermore, this relationship is less pronounced if family firms operate in industries with high research and development intensity. Our study confirms that boards with high shares of religiously perceived directors are positively associated with the appointment of chief executive officers perceived to be religious during succession events. We thereby present a unique perspective that acknowledges perceived religiosity as a micro-level constituent shaping board membership and successor selection. This investigation captures the intricate interplay between religion and family firms under a socioemotional wealth umbrella, offering important insights to the family business ethics discourse. Our research also offers practical implications for board and leadership diversity management in family firms.
Keywords: 300; Family firms; Socioemotional wealth; Religious managers; Board of directors; Chief executive officer; Religious diversity